Learning of the central tendency measures through the tool eXeLearning - Valia Dalgis Cordoví Hernández; Vivian Benito Valenciano; Luanda Pruna Serrano; Alcides Muguercia Bles; José Antúnez Coca (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive and cross-sectional study of 24 students from the health statistics specialty, belonging to the Nursing-technology Faculty in Santiago de Cuba was carried out from December, 2016 to March, 2017, in order to determine the feasibility of eXeLearning  as a computing science tool.  The usefulness of this tool was shown as a learning object in the learning and training of knowledge of central tendency measures, in series of simple data for the practical classes and  independent study, with a high degree of independence in searching and recovering information.  The development of an autonomous and net learning was achieved in the students, which follows the multidisciplinary training in the medical education.